Associations between serum relaxin 2, aneurysm formation/size and severity of atherosclerosis: a preliminary prospective analysis. - Papoutsis, Konstantinos; Kapelouzou, Alkistis; Tsilimigras, Diamantis I; Patelis, Nikolaos; Kouvelos, Georgios; Schizas, Dimitrios; Karavokyros, Ioannis; Georgopoulos, Sotirios (Acta Pharmacol Sin, 2018)
Serum relaxin 2 (RL2) is a pleiotropic hormone that acts on various organs and systems, particularly the cardiovascular system. Although RL2 seems to upregulate the synthesis of nitric monoxide (NO) and matrix metalloproteinase (MMP)-2 and -9, current literature on its role in atherosclerosis and aneurysm formation is scarce. The aim of this study was to investigate the levels of serum RL2 in patients with an arterial aneurysm as well as in atherosclerotic patients, and correlate them with the severity of their related vascular disease. A total of 53 subjects were enrolled in this study: 37 patients were scheduled to undergo surgery: 21 patients for different forms of atherosclerotic disease (ATH), 16 patients for an arterial aneurysm (AA), 6 patients for undergoing temporal artery biopsy (TAB), and 10 healthy blood donors (HBD) served as the control groups. RL2 was measured using enzymelinked immunosorbent assay. RL2 was significantly higher in AA patients compared to ATH (P<0.01), TAB (P<0.001) and HBD (P<0.01). No significant difference was found between the ATH and TAB groups (P>0.05). In addition, ATH and AA patients were further subdivided based on the severity of their disease. Serum RL2 was progressively increased in patients with arterial aneurysms, showing a positive relationship with the size of the aneurysmatic dilatation. By contrast, the RL2 level was inversely related to the severity of the atherosclerotic disease. Studies with a larger cohort incorporating a consistent study population are warranted to verify our results and shed light on the mechanistic background of these processes.